Changes of the optical characteristics of radiochromic films in the transition from EBT3 to EBT-XD films. (1st July 2016) - Schoenfeld, Andreas A; Wieker, Soeren; Harder, Dietrich; Poppe, Bjoern
Abstract: A new type of radiochromic film, the EBT-XD film, has been introduced with the aim to reduce the orientation effect and the lateral response artifact occurring in the use of radiochromic films together with flatbed scanners. The task of the present study is to quantify the changes of optical characteristics involved with the transition from the well-known EBT3 films to the new EBT-XD films, using the optical bench arrangement already applied by Schoenfeld et al (031 Phys. Med. Biol .59 3575–97). Largely reduced polarization effects and the almost complete loss of the anisotropy of the scattered light produced in a radiation-exposed film have been observed. The Rayleigh–Debye–Gans theory is used to understand these optical changes as arising from the reduced length-to-width ratio of the LiPCDA polymer crystals in the active layer of the EBT-XD film. The effect of these changes on the flatbed scanning artifacts will be shortly addressed, but treated in more detail in a further paper.